Non-viral HCC miRNA profiling reveals miR-1972 as a potential positive prognostic marker - Venkata Ramana Mallela; Marie Rajtmajerová; Esraa Ali; Lenka Červenková; Andriy Trailin; Petr Hošek; Richard Pálek; Ondřej Daum; Václav Liška; Kari Hemminki; Filip Ambrozkiewicz (Non-coding RNA Research)
Background & Aims: Hepatocellular carcinoma (HCC) is the third deadliest cancer worldwide. Its high mortality is primarily attributed to late-stage diagnosis. While mutations in driver genes, such as those encoding β-catenin (CTNNB1), tumor protein p53 (TP53), and telomerase reverse transcriptase promoter (TERTp) are well-documented in the literature, dysregulation of microRNAs (miRNAs), small non-coding RNAs that serve as crucial translational regulators, remains poorly understood. Methods: We conducted microRNA profiling by microarrays in 45 paired (tumor and non-tumor adjacent tissue) samples from non-viral HCC patients. We performed clinical correlation, ROC analysis and survival analysis of time to recurrence (TTR), disease-free survival (DFS) and overall survival. Results: We identified 23 significantly dysregulated miRNAs (p ≤ 0.05, fold change ≥2). We investigated their differential expression and its relationship with clinical and pathological variables. Further, we found that miRNA-1972 may serve as an important positive prognostic marker because its high levels were associated with longer TTR and DFS. Significant positive results were obtained in receiver operating characteristic analysis for miR-1972, miR-3651 and miR-486–5p. Conclusion: miRNA-1972 is a strong prognostic marker in non-viral HCC. Dysregulation of several other miRNAs relates to pathological variables such as amount of stroma within tumor, microvascular invasion and micronodularity.